Macrophage-stimulating activity of European eel (Anguilla anguilla) peptides in RAW264.7 cells mediated via NF-κB and MAPK signaling pathways. Issue 12 (7th December 2020) - Yao, Lijun; Yang, Peng; Luo, Wenqi; Li, Shuiming; Wu, Yan; Cai, Nan; Bi, Decheng; Li, Hui; Han, Qingguo; Xu, Xu
Abstract : This is the first study to investigate the immunostimulatory effect of eel peptide (EP) from Anguilla anguilla in RAW264.7 cells, and the most effective component of EP mainly consisted of collagen-derived Hyp-containing peptides. Abstract : European eel ( Anguilla anguilla ) is considered to be a vital commercial fish species. In this study, the effect and molecular mechanism of bioactive peptides from European eel on macrophage-stimulating activity in RAW264.7 cells were investigated. Eel peptide (EP) markedly induced NO and iNOS production and promoted TNF-α and IL-6 secretion in a concentration-dependent manner. Moreover, EP dose-dependently activated NF-κB and MAPK signaling pathways in RAW264.7 cells. In addition, EP was purified using a Sephadex A-25 column and a Bio-Gel P -6 column, and the fraction (Fr-1-1) showing the strongest NO-inducing activity was obtained. Then, the molecular weights of the components in Fr-1-1 were analyzed by LC-MS/MS and found to range from 700 to 1900 Da for the majority of components, which suggested that Fr-1-1 mainly consisted of peptides containing 8–20 amino acid residues. Overall, our results indicated that EP from Anguilla anguilla activated macrophages and could be used as a potential nutraceutical or pharmaceutical.